2016
DOI: 10.1097/aln.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Adductor Canal Block Provides Noninferior Analgesia and Superior Quadriceps Strength Compared with Femoral Nerve Block in Anterior Cruciate Ligament Reconstruction

Abstract: Background By targeting the distal branches of the femoral nerve in the mid-thigh, the adductor canal block (ACB) can preserve quadriceps muscle strength while providing analgesia similar to a conventional femoral nerve block (FNB) for inpatients undergoing major knee surgery. In this randomized, double-blind, noninferiority trial, the authors hypothesized that ACB provides postoperative analgesia that is at least as good as FNB while preserving quadriceps strength after outpatient anterior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
133
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 56 publications
4
133
3
Order By: Relevance
“…Our study results do not contradict the recently published study by Abdallah et al (16), which showed that ACB was not inferior to FNB for analgesia following arthroscopic repair of the anterior cruciate ligament while preserving muscle strength. Using the weaker clinical criteria and combining it with preserved anterior muscle strength allowed the authors to reach a conclusion of non-inferiority in providing postoperative pain relief.…”
Section: Discussioncontrasting
confidence: 55%
“…Our study results do not contradict the recently published study by Abdallah et al (16), which showed that ACB was not inferior to FNB for analgesia following arthroscopic repair of the anterior cruciate ligament while preserving muscle strength. Using the weaker clinical criteria and combining it with preserved anterior muscle strength allowed the authors to reach a conclusion of non-inferiority in providing postoperative pain relief.…”
Section: Discussioncontrasting
confidence: 55%
“…Expectedly, in both studies, patients randomized to the former displayed superior quadriceps strength as assessed by straight leg raise during the first 24 hours392 or maximal voluntary isometric contraction at 45 min 393. However, the findings pertaining to pain control differed between the two trials.…”
Section: Controversial Areas Related To Outcomesmentioning
confidence: 87%
“…Whereas Abdallah et al 393 found that femoral triangle/adductor canal blocks resulted in non-inferior analgesia and opioid consumption compared to femoral blocks, El Ahl392 reported lower pain scores (at 18 and 24 hours) as well as decreased morphine consumption in patients receiving femoral blocks. This discrepancy could be attributed to the nature of the graft: patellar392 versus hamstring or bone–tendon–bone 393. Nonetheless, in light of these contradictory results, additional trials are needed to compare femoral triangle/adductor canal and femoral blocks for the different types (grafts) of ACL repair.…”
Section: Controversial Areas Related To Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…In their 54 patient series, both groups were shown to be similar in terms of opioid consumption [7]. Similarly, in a series of 100 patients undergoing anterior ligament repair, adductor canal block and femoral nerve block were found to be equal in terms of cumulative oral morphine consumption [15]. In the same way as our subjects, Dong et al [16] reported that adductor canal block (ACB) shows no superiority than femoral nerve block (FNB) group regarding muscle strength and pain control.…”
Section: Discussionmentioning
confidence: 99%